Analysis of the incidence of chd and resource care of cardiac patients in the North Сaucasus federal district and Karachay-dierkessia - K. R. Amlaev; R. U. Aibazov; V. B. Zafirova (Кубанский научный медицинский вестник, 2014)
The article presents the results of the analysis incidence of ischemic health diseases in Russia, North Caucasus federal district and Karachay-Cherkessia republic by federal statistical observation forms. The differences were found in the incidence of cardiovascular disease outcomes between regions. The significance of the availability of cardiology and cardiac care to improve the health of residents of the region was shown.